2011
DOI: 10.1056/nejmoa1012348
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and Short-Term Androgen Deprivation for Localized Prostate Cancer

Abstract: Among patients with stage T1b, T1c, T2a, or T2b prostate adenocarcinoma and a PSA level of 20 ng per milliliter or less, the use of short-term ADT for 4 months before and during radiotherapy was associated with significantly decreased disease-specific mortality and increased overall survival. According to post hoc risk analysis, the benefit was mainly seen in intermediate-risk, but not low-risk, men. (Funded by the National Cancer Institute; RTOG 94-08 ClinicalTrials.gov number, NCT00002597.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
406
1
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 632 publications
(440 citation statements)
references
References 34 publications
10
406
1
16
Order By: Relevance
“…The use of long-term hormone therapy in combination with conventional doses (65-70 Gy) of external beam radiation therapy has been shown to contribute to improved therapeutic outcomes in patients with localized prostate cancer, particularly those at high risk, whereas short-term neoadjuvant hormone therapy is believed to contribute to improved therapeutic outcomes in patients at moderate risk. [17][18][19][20][21][22][23][24] However, the evidence for these indications is based on radiation doses of 65-70 Gy, and the value of ADT in combination with !76 Gy radiation doses remains unclear. Opinions on this point are divided, as some studies have found no association between ADT and therapeutic outcomes of !76 Gy IMRT, whereas others have reported improved DMFS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of long-term hormone therapy in combination with conventional doses (65-70 Gy) of external beam radiation therapy has been shown to contribute to improved therapeutic outcomes in patients with localized prostate cancer, particularly those at high risk, whereas short-term neoadjuvant hormone therapy is believed to contribute to improved therapeutic outcomes in patients at moderate risk. [17][18][19][20][21][22][23][24] However, the evidence for these indications is based on radiation doses of 65-70 Gy, and the value of ADT in combination with !76 Gy radiation doses remains unclear. Opinions on this point are divided, as some studies have found no association between ADT and therapeutic outcomes of !76 Gy IMRT, whereas others have reported improved DMFS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suitable for ADT should be given combined doseescalated IMRT (76-78 Gy) with short-term ADT (4-6 months) [68]. For patients unsuitable for ADT (e.g.…”
Section: Intermediate-risk Pcamentioning
confidence: 99%
“…The evidence for short-term NHT plus RT compared with RT alone is supported by several studies. [4][5][6][7][8] In the RTOG 86-10 trial, the combination of goserelin plus flutamide for 2 months before RT and concurrent with RT was evaluated in patients with locally advanced PCa (bulky T2-4 tumors with or without pelvic lymph node involvement). 29 NHT significantly improved diseasespecific survival versus the use of RT alone.…”
Section: Long-term Adjuvant Adt Plus Rt Versus Adt Alonementioning
confidence: 99%
“…1). 6 Two randomized controlled trials (RCTs) demonstrated that 6 months of NHT also improved OS compared with RT alone. 4,5 In the first study, the addition of 6 months of NHT/concurrent/adjuvant ADT to RT also conferred an OS benefit versus RT alone.…”
Section: Long-term Adjuvant Adt Plus Rt Versus Adt Alonementioning
confidence: 99%